PENGARUH PERCEIVED SCARCITY DAN PERCEIVED VALUE TERHADAP PURCHASE INTENTION PEMBELI GAME OF LIMITED-AMOUNT VERSION DI SURABAYA - Antonio Hercento; Christina R. Honantha; Silvia Margaretha (CALYPTRA, 2018)
Abstract – Game is a rapidly developing industry in the worldwide, including Indonesia. But the high piracy rate in Indonesia itself is harming the profit of the domestic gaming companies, and to prevent further damages, game of limited- amount version is one of the solutions. Therefore, this study aims to explore the impact of perceived scarcity and perceived value toward buyers’ purchase intention of game of limited-amount version. The results of this study is to provide insights and recommendations for the decision making of gaming companies in Indonesia. This study uses quantitative approach and the data collection is done by surveying, where 200 questionnaire is distributed to respondents whose domiciled in Surabaya and bought game of limited-amount version at least once in the past 6 months. The findings in this study shows that perceived scarcity, in an indirect way, does affect perceived value. Then perceived value has a direct impact toward buyers’ purchase intention of game of limited-amount version in Surabaya.